An OGSA-based Integration of Life-scientific Resources for Drug Discovery - Kosaka, T.; Tohsato, Y.; Date, S.; Matsuda, H.; Shimojo, S. (Methods of Information in Medicine, 2005)
Objectives: The rapid progress of life-scientific research has the potential to dramatically change the paradigm of drug discovery. Efficient utilization of life-scientific resources, i.e., databases and analytic software tools, poses a challenging issue with regard to the reduction of time and cost in the drug discovery process. In this paper, a variety of heterogeneous Web-based life-scientific resources are integrated toward the improvement of drug discovery performance.Methods: For the integration of heterogeneous life-scientific resources, a database federation technique based on three-layer architecture has been utilized. With the federation technique, life-scientific resources are integrated step by step through database layers, database integration layers and analysis layers to encapsulate complexity and heterogeneity. In this study, we have taken advantage of the latest Grid technology based on OGSA (Open Grid Services Architecture) for the implementation of our approach.Results: The actual case of life-scientific resources for drug discovery demonstrates that our prototype system developed with the proposed technique works well for the identification process of candidate compounds to a target protein. In other words, the prototype system allows a researcher to retrieve candidate compounds with less effort than before.Conclusions: The usefulness of the prototypic system represents the ability of our approach to integrate heterogeneous life-scientific resources, which have the potential to dramatically improve efficiency in drug discovery, resulting in the shortening of drug development. On the other hand, the system requires further consideration from the aspect of practical use. Dynamic aggregation of the resources is one example of such a consideration.
Keywords: Drug discovery; life sciences; Open Grid Services Architecture